1991
DOI: 10.1093/oxfordjournals.jbchem.a123606
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of 1,200 kDa Peptide of α-Connectin1

Abstract: When rabbit skeletal muscle myofibrils were kept for 12 h at 4 degrees C, alpha-connectin was partially degraded and 1,200 kDa peptide was newly formed [Takahashi, K. & Takai, H. (1988) Abst. 80th Jpn. Soc. Zootech. Sci. p-102]. The latter was isolated together with remaining alpha-connectin. Ultracentrifugation of the mixture at low ionic strength resulted in sedimentation of alpha-connectin, leaving the 1,200 kDa peptide in the supernatant. Physicochemical properties of the isolated 1,200 kDa peptide were in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

1993
1993
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 0 publications
3
22
0
Order By: Relevance
“…results herein with those in Lusby et al, 1983;Zeece et al, 1986;Fritz and Greaser, 1991;Fritz et al, 1993). This was necessary to help reduce the confusion that can occur when inadequate separation causes high-molecularweight titin degradation products (e.g., the 1,200 kDa band of Matsuura et al, 1991) to migrate very closely to T2 or nebulin. The system used in our study ( 5 % separating gel, acrylamide:N,N-bis-methylene acrylamide = 100: 1) also permitted easier identification of the TI and T2 bands due to their greater separation (Huff-Lonergan et al, 1994).…”
Section: Discussionmentioning
confidence: 93%
“…results herein with those in Lusby et al, 1983;Zeece et al, 1986;Fritz and Greaser, 1991;Fritz et al, 1993). This was necessary to help reduce the confusion that can occur when inadequate separation causes high-molecularweight titin degradation products (e.g., the 1,200 kDa band of Matsuura et al, 1991) to migrate very closely to T2 or nebulin. The system used in our study ( 5 % separating gel, acrylamide:N,N-bis-methylene acrylamide = 100: 1) also permitted easier identification of the TI and T2 bands due to their greater separation (Huff-Lonergan et al, 1994).…”
Section: Discussionmentioning
confidence: 93%
“…A major degradation product that migrates only slightly faster under SDS-PAGE conditions than T1 is termed T2 (approximately 2,400 kDa) (Kurzban and Wang, 1988). Another titin degradation product that has been observed migrates at approximately 1,200 kDa by SDS-PAGE analysis (Matsuura et al, 1991;Takahashi et al, 1992). This latter polypeptide has been shown to contain the portion of titin that extends from the Z-line to near the putative N 2 line in the I-band (Kimura et al, 1992;Kawamura et al, 1995), although the exact position that the 1,200-kDa polypeptide reaches in the sarco-mere is still not certain.…”
Section: Titinmentioning
confidence: 99%
“…The following polyclonal (pAbs) and monoclonal antibodies (mAbs) were used: anti-connectin pAb against 1,200 KDa peptide of a-connectin (P1200) (Matsuura et al, 1991) and mAb 4C9 (Matsuno et al, 1989); anti-myosin pAb (Transformation Research Inc., Framingham, MA) and mAb MF20 (Masaki et al, 1982); anti-a-actinin pAb (Endo and Masaki, 1984) and mAb BM-75.2 (BioMakor, Rehovot); and anti-troponin C (TnC) pAb (Toyota and Shimada, 1981). Secondary antibodies were FITC-or rho-labeled anti-rabbit, anti-mouse, or antigoat IgG (Cappel Laboratories) and rho-labeled antimouse IgG (Tago, Inc., Burlingame, CA).…”
Section: Fluorescence Microscopymentioning
confidence: 99%
“…6 ) . Previous studies have shown that the membrane areas where actin filaments of myofibrils and stress fibers anchor exhibit proteins such as vinculin, a-actinin, and talin Using two Abs that recognize distant domains of connectin filaments, mAb 4C9 which binds the edges of the A band domain of connectin filaments (Matsuno et al, 1989) and pAb P1200 which binds the I band near the Z line (Matsuura et al, 1991), we monitored the devel-…”
Section: Incorporation Of Microinjected Biotin-actin Into Nascent Myomentioning
confidence: 99%
See 1 more Smart Citation